236 USE OF GUIDEBOOK AND BRIEF INSTRUCTION TO INCREASE DIABETES SELF-MANAGEMENT. Issue 1 (1st January 2007) - Bocchini, M. V.; Davis, K.; Joyner, J.; Wallace, A. S.; Seligman, H.; DeWalt, D.; Schillenger, D.; Arnold, C. L.; Davis, T. C.; Delgadillo, A.
Abstract : Purpose: To evaluate a patient-centered diabetes self-management guide augmented with brief instruction to assist patients in making behavior changes to improve their diabetes. Methods: We performed a pre- and a postintervention in a convenience sample of English-speaking patients with type 2 diabetes in two university medicine clinics (LSUHSC-S and UNC). A trained research assistant (RA) administered a baseline questionnaire to assess diabetes knowledge, self-efficacy, behaviors, and reading ability. RAs gave each patient a diabetes self-management guide (fourth-grade reading level), which gives practical strategies to improve eating, exercise, monitoring, and medication adherence. The RA then gave each patient brief instruction on how to make an action plan (AP) and assisted them in establishing a patient-generated short-term AP. The RA followed up with each patient at 2 weeks and 4 weeks postenrolment, calling to discuss use of the guide and adherence to the AP. Results: 150 patients were enrolled, ranging in age from 30 to 86 years; 67% were female, 66% African American, and 31% white; 34% had inadequate literacy. Patients had been diagnosed with diabetes from 30 days to 27 years. The introduction of the guide and AP instruction took an average of 5 to 10 minutes. To date, 106 patients have been called at 2 weeks and 78 at 4 weeks. Patients indicated that the guide was easy to understand and use. They said that it was different from any diabetic material they had received as it had more information they wanted to know. They identified with the real people in the pictures and liked the colorful photographs rather than black and white photocopies. At 2 weeks, 94% of patients remembered their AP and 77% indicated that they adhered to it. At 4 weeks, 100% remembered their AP and 89% indicated that they adhered to it (thus making a behavior change). Most APs involved limiting a certain food or doing a simple exercise. Example APs are "I will walk to my mailbox 4 times a week" or "I will dance in the kitchen with my godbaby for 2 to 3 songs." One patient's first AP was to bring a healthy snack to work instead of getting food from the vending machine. By the second telephone call, she said that she had gained such confidence from achieving her first AP that she had decided to quit smoking for her final AP. Conclusion: A patient-centered diabetes self-management guide with brief instruction in making action plans and telephone follow-up facilitated behavior change and improved diabetes self-management.